Hydrophobic modification of chitosan nanoparticles for increased therapeutic delivery and anticancer properties towards human cancer cell lines - Cha, Yee Kuen (2020)
Lung cancer is the leading cause of cancer-related deaths for men and second for women worldwide, with approximately 1.6 million of deaths reported annually. Conventional delivery of anticancer drugs for treatment is less effective due to intrinsic obstacles such as poor aqueous solubility and poor cellular accumulation of drugs. Additionally, chemotherapy incurs various concomitant undesirable side effects including cytotoxicity, cardiotoxicity and neurotoxicity. Thus, the utilization of natural anticancer therapeutics as an alternative is required to prevent these undesirable consequences. Silibinin (SLB) is a poorly-soluble plant extract derived from Silybum marianum which is commonly used for treatment of liver diseases. SLB exhibits anti-cancer properties by inhibiting cell growth, angiogenesis, proliferation, cell migration and inducing apoptotic death. However, poor solubility and cell accumulation of SLB limits the use of this compound as an alternative anticancer therapeutic. Therefore, the employment of nanotechnological-based applications have aided in the advancement of better diagnosis and more efficient treatment of cancer. Additionally, the utilization of nanoparticulate delivery can reduce the dosage of the natural therapeutic compound, reducing potential side effects of therapeutics. Based on the results, a low encapsulation efficiency was achieved by conventional chitosan nanoparticle (CNP) system. This necessitates modification of the CNP through hydrophobic modification to develop a palmitoylchitosan nanoparticle (pCNP) system for enhanced encapsulation efficiency and therapeutic efficacy. Various physico-chemical characterization analyses was conducted to evaluate the pCNP system. Utilization of free amine percentage of pCNP increased by 15% due to the conjugation of –NHS palmitic acid to the polymer, in addition to TPP. The pCNP synthesized revealed an expansion in size and decrease in polydispersity index (PDI) compared to CNP, indicating greater monodispersity in pCNP. The encapsulation of SLB into pCNP showed an expansion in size and PDI, signifying the heterogeneity of nanoparticles after encapsulation and correlating to morphological analyses. Moreover, the encapsulation efficiency improved 1-fold from 25% of CNP-SLB to 50% of pCNPSLB. Subsequently, MTT cytotoxicity assay showed enhanced efficacy of pCNPSLB over CNP-SLB and free SLB. It was found that pCNP-SLB was most competitive in A549 cell line compared to SW620 and 786-O cell lines as shown by the lowest IC50 value of 7.77 μM among different cancer cell lines and time points. Further study conducted using A549 cell line has demonstrated that pCNPSLB has enhanced the anti-invasive effect of SLB through cell migration assay and suggested the synergistic effect between pCNP and SLB. On the other hand, Annexin V apoptosis assay and cell cycle analysis have also shown that pCNPSLB revealed a correlated results of enhanced apoptotic death and G1 cell cycle arrest in A549 cells with sustained release properties. These results have therefore revealed the enhanced therapeutic efficacy and sustained release properties of pCNP-SLB which required low dosing to achieve high therapeutic efficacy. Additionally, subsequent study on pCNP encapsulation on protocatechuic acid (PCA) has revealed that pCNP can be utilized to other poorly soluble compounds other than SLB. Conclusively, various physico-chemical analyses have indicated the modification on CNP system and signified the successful encapsulation of SLB into pCNP. Besides, the in vitro cellular study has suggested an enhanced therapeutic efficacy of pCNP-SLB compared to conventional CNPSLB and free SLB towards A549 cells with sustained release properties. This system can potentially be developed into novel delivery system for many other hydrophobic therapeutics to aid in pharmaceutical and biomedical fields.